Isolation and Characterization of Xylanase from a Novel Strain, Penicillium menonorum SP10 - Thi Thu Huong Luong; Supattra Poeaim; Narumon Tangthirasunun (My University, 2023)
Xylanase has been applied in various sectors, such as biomass conversion, paper, pulp, textiles, and pharmaceutical industries. This study aimed to isolate and screen potential xylanase-producing fungi from the soil of Suphan Buri Province, Thailand. Fifteen fungi were isolated, and their xylanase activities were tested by the qualitative method. The result showed that isolate SP3, SP10 and SP15 gave high xylanase activity with potency index (PI) of 2.32, 2.01 and 1.82, respectively. These fungi were selected for the xylanase quantitative test, isolate SP10 performed the highest xylanase activity with 0.535 U/mL. Through molecular methods using the β-tubulin gene, isolate SP10 was identified as Penicillium menonorum. The xylanase characteristics from P. menonorum SP10 were determined, including the xylanase isoforms and the optimum pH and temperature. The xylanase isoforms on SDS-PAGE indicated that P. menonorum SP10 produced two xylanases (45 and 54 kDa). Moreover, its xylanase worked optimally at pH 6 and 55 °C while reaching 61% activity at 65 °C. These results proposed P. menonorum SP10 as a good candidate for industrial uses, especially in poultry feed and pulp industries, to improve yield and economic efficiency under slightly acidic and high-temperature conditions.
Keywords: Biofuel production and bioconversion